Neonatal TSH levels in Northern Ireland from 2003 to 2014 as a measure of population iodine status. (8th October 2018) - Mullan, Karen; Patterson, Chris; Doolan, Katy; Cundick, Jennifer; Hamill, Lesley; McKeeman, Gareth; McMullan, Paul; Smyth, Peter; Young, Ian; Woodside, Jayne V.
Abstract: Objective: The re‐emergence of iodine deficiency in the UK has recently been reported in a large cohort of teenage girls including from Northern Ireland (NI) using the gold standard spot urinary iodine concentration. We wished to explore and confirm this by analysing neonatal thyroid‐stimulating hormone (nTSH) levels in the NI population. Design: We analysed the nTSH heel prick tests results from the NI national screening database between 2003 and 2014. The WHO proposes a definition for population iodine sufficiency at <3% of the population with nTSH results >5 mIU/L. Methods: Anonymized results from 288 491 nTSH tests were retrieved, and prevalence rates of results at increasing cut‐offs including >2 mIU/L and >5 mIU/L calculated. We also assessed for possible seasonal variation in nTSH results. Results: An overall population prevalence of 0.49% with TSH >5 mIU/L was found, indicating population iodine sufficiency with no year attaining a prevalence >3%. The prevalence of nTSH >2 mIU/L decreased to 4.1% in 2007 and subsequently increased to 9.8% in 2014. Modest seasonal variation was also detected, with higher levels among April/May births. Conclusions: The neonatal TSH database suggests iodine sufficiency in the NI population. However, the rising frequency of results >2 mIU/L may indicate an emerging mild iodine deficiency. This is one of the largest and longest studies of its kind in the UK and the first carried out in NI. The summer months may be a time of increased risk of iodine deficiency in our pregnant women whose requirements are increased and who are not currently targeted by any iodine fortification programme in the UK.